Chemical equations - Lines, Jeremy; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2005)
Explain what chemical equation are , how they're written and how we balance them . Discusses combination , decomposition , replacement and combustion
Executive producer , Mark McAuliffe ; writer , associate producer , Simon Garner ; camera , Michael Henry ; sound, Wayne Martin
For middle secondary to senior secondary students
Keywords: Chemical equations; Chemical reactions; Chemistry